Patient perspectives on the care in a long COVID outpatient clinic: a regional qualitative analysis from Germany - Gölz, Lea; Poß-Doering, Regina; Merle, Uta; Wensing, Michel; Stengel, Sandra (Healthcare, 2025)
Background/Objectives: Long COVID specialized outpatient clinics (sOCs), which are part of the recommended long COVID care, usually face high demand. Few studies focused on the experience of care in such facilities in Germany. This study investigated how patients experience care in a sOC at a German university hospital. Methods: Semi-structured interviews were conducted with patients attending this clinic between October 2022 and January 2023. Data analysis was based on thematic analysis. Results: The themes from interviews with 14 patients (F = 11, M = 3) could be broadly categorized into statements on the pathway to the sOC, and statements on care provided in the sOC. Findings show that patients’ high expectations at the sOC appointment were shaped by previous experiences with care, which were mainly perceived as inadequate. Care in the sOC was predominantly perceived as competent, empathetic and relevant for further care and coping with the disease. A deterioration in health directly related to the consultation (classifiable as post-exertional malaise) was frequently described, as was a high need for ongoing consultation. Conclusions: Overall, the findings point to a need for adaptations in the sOC, such as identifying optimized models of care and tailoring them to the patients’ limited resources. This includes measures to improve care outside the sOC.